Exploration of the Da'wah Message in the Popular Song “Alamate Anak Sholeh” / Eksplorasi Pesan Dakwah Pada Lagu Populer "Alamate Anak Sholeh" - Ulfa Ni'amah, Luthfi; Pratiwi, Clara Sinta; Cahyono, Muchamad Rudi (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2024)
Da'wah using the medium of songs is being loved among society, especially among young people. None other than the supporting factors of technology and the reach of access in the digital world are increasingly massive. The song entitled "Alamate Anak Sholeh" which is taken from the book Busyrol Karim written by Syaikh H. Rois Yahya Dahlan As Syarof is distributed through various social media platforms, one of which is. So the aim of this research is to see that deeper meaning is needed to understand and absorb the message of Islamic values. Using Charles Sanders Pierce's semiotic method is appropriate to describe the signs contained in each stanza. The results of the categorization of Sharia preaching messages show the message that it is the obligation of a Muslim to believe and follow the Shari'a, the moral category that dominates the lyrics is the four characteristics of pious children, and the Sufism category that every creature needs dependence on Allah SWT.